Training Profession for Law Career on Facing ASEAN Economic Community Era: Improving the Law Graduates through Development of Legal Education Method - Farah Diba Khotijah; Anas Mawardi; Inayatus Sholihah (The Indonesian Journal of International Clinical Legal Education, 2019)
The ASEAN Economic Community (AEC) stands as one of Southeast Asia's predominant market shares, facilitating international trade in products and services among its ten member countries. This integration enables the free movement of goods and services within the Southeast Asian region, posing challenges to Indonesia's human resources (HR) and employment landscape. The heightened competition among graduates in the AEC era adds complexity to the employment scenario. Law graduates, in particular, face distinctive challenges in this environment. According to BPS 2016 data, over 2500 graduates struggled to secure suitable employment or career opportunities. Addressing this issue necessitates a strategic evolution in legal education, with a focus on initiatives like the Training Profession for a Law Career. This training, administered by university-formed professional training institutions, caters to law graduates who opt not to pursue advanced degrees (master program) and seeks direct orientation towards societal integration and the workforce. The training program mandates a practical experiential phase for law graduates, allowing them a certain period to experiment within the profession. Subsequently, graduates are afforded the freedom to either deepen their professional involvement or transition directly into the community. By bolstering education and skill enhancement, this approach aims to elevate labor productivity, thereby contributing to the overall enhancement of national competitiveness.